PENGARUH PENGGUNAAN SABUT BUAH KELAPA SAWIT AMONIASI DALAM RANSUM SAPI PERAH TERHADAP KECERNAAN IN-VITRO - Agung Kusuma Wijaya (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
The experiment was conducted at the Animal Nutrition Laboratory and field laboratory, Animal Husbandry faculty, Brawijaya University Malang for making the oil palm fruit fiber amoniasi and analysis of nutrient content and digestibility in vitro is carried out from July to August 2011. The purpose of this study to determine the effect of differences in the level of use urea and palm amoniasi as a forage substitute. To get the optimum level of use of oil palm fruit fiber amoniasi that gives the best response to digestibility in vitro. The results are expected to be used as information about the utilization of oil palm fruit waste as an alternative to cattle feed.  Materials on research are oil palm fruit fiber and urea as a feed ingredient substitutions. The research method is experimental by design Factorial Randomized Block Design, study the influence of the addition of urea level and duration of incubation in the oil palm fruit fiber for nutrient content and digestibility in vitro. Variables measured, a research study nutrient content, digestibility of DM (Dry matter) and digestibility of OM (Organic matter) of oil palm fruit fiber amoniasi. Data were analyzed by variance and if the real test followed by Duncan.  The results of the research showed that the addition of urea level and duration of incubation significant effect (P <0.05) to 50.61% DM and 48.23 % OM which is in P2.  It can be concluded that use 50 % corn plant and 10% of oil palm fruit fiber and digestibility optimum at DM and OM. Suggested the use of oil palm fruit fiber is to field research to know how impact in dairy cattle. Key words: Amoniasi, In Vitro, Oil Palm Fruit Fiber